Impact of a Tiered Referral System on Outpatient Satisfaction under BPJS Kesehatan: A Case Study at dr. Slamet Regional General Hospital Garut - Rahmannisa, Shofa Nur; Aspiranti, Tasya; Suyanto, Rachmat (Journal of Social Science and Business Studies, 2025)
This study aims to analyze the satisfaction levels of outpatients participating in Indonesia's national health insurance (JKN) under its tiered referral system. The research objective is to assess patient satisfaction at Dr. Slamet Regional Public Hospital, a primary referral center, across six key dimensions. A mixed-methods approach was employed, using surveys with 105 outpatients and in-depth interviews with hospital personnel. The findings reveal an overall patient satisfaction level of 74.01%, classified as “good.” Medical services received the highest satisfaction score (76.62%), while cost perception was the lowest (69.14%). Although clinical care is highly rated, the study identifies significant administrative complexity and long waiting times as primary sources of patient dissatisfaction. The main implication is that while the JKN program succeeds in delivering quality medical care, the patient experience is significantly hampered by bureaucratic inefficiencies. Practical improvements should focus on streamlining administrative procedures and optimizing patient flow to enhance overall satisfaction.